Pigeon breeder's disease: the clinical spectrum and humoral response; an investigation of the nature and extent of extrinsic allergic alveolitis due to pigeon-derived antigens among pigeon fanciers continuing to pursue the pastime, with particular reference to early clinical and humoral-mediated responses following exposure - Banham, Stephen Walter (The University of Edinburgh, 1986)
This thesis examines the relationships between the clinical manifestations of Pigeon Breeder's Disease among active pigeon fanciers, and the associated humoral responses to pigeon -derived antigens. Clinical data was obtained in questionnaire format from a large scale field study interviewing 100 pigeon fanciers. A wide range of skin tests were performed and serum antibodies were estimated by sensitive and quantitative radioimmunoassay techniques. Selected pigeon fanciers also underwent detailed pulmonary physiological assessments including monitoring of lung function after antigen challenge. In particular, immediate components of the condition both clinical and immunological have been investigated.

Simple criteria have been formulated to categorise pigeon related clinical responses and a wider spectrum of Pigeon Breeder's Disease was identified. Modifications to the current classification are suggested to encompass -

1) acute progressive disease - the typical acute hospital referred case

2) acute recurrent disease - recurrent,febrile, alveolitis episodes but without short or medium term clinical deterioration. Affected persons continue active participation in the hobby and therefore this is probably more common than acute progressive disease with a prevalence of approximately 10% in the present studies. Self regulation of exposure is an important aspect.

3) Immediate Response - consisting of 3 or more immediate symptoms; commonly recorded among pigeon fanciers, often with delayed symptoms forming an indistinct group that did not represent a specific clinical or immunological entity 4) chronic PBD - evidence was found suggesting that chronic respiratory symptoms are an important part of the clinical spectrum occurring in up to 20% of non -smokers.

The pulmonary function data supported these clinical distinctions and lung permeability studies showed disturbed physiological integrity even where routine pulmonary function parameters were normal. This technique merits further investigation as a potentially sensitive indicator of physiological abnormality in extrinsic allergic alveolitis.

Relationships between avian- specific IgG, exposure factors and clinical response have been extended. There was a progressive tendency towards an altered immune reactivity (immunisation) as certain parameters of exposure increased,but this did not correlate with a major likelihood for finding extrinsic allergic alveolitis. High antibody responders are a group determined by host immunological responsiveness. An intense IgG response correlated with the presence of Pigeon Breeder's Disease independently of exposure,and those having >60ug /ml serum IgG to pigeon globulin evident within 10 years of pigeon keeping were particularly likely to report acute Pigeon Breeder's Disease.

The skin test data indicate that the humoral immune response routinely includes reaginic activity which relates to IgG antibody rather than IgE and such responses were associated with the presence of extrinsic allergic alveolitis independently of the late,6 hour,intradermal response.

These studies redefine the clinical spectrum of Pigeon Breeder's Disease and establish that there is a dynamic interaction between exposure and symptoms constituting a self - regulation of the condition particularly relevant in those persons with acute recurrent disease. A close relationship between avian-specific IgG and Pigeon Breeder's Disease has been reaffirmed and shown to relate primarily to factors other than intensity of exposure,and to have a functional capability including reaginic activity. The findings favour an active role for antibody in the immunopathogenesis of Pigeons Breeder's Disease and it is postulated that avian- specific reaginic activity within the pulmonary compartment may initiate or enhance other immune events leading in susceptible persons to the disease entity of extrinsic allergic alveolitis.